Transforming growth factor β1 and laminin-111 cooperate in the induction of interleukin-16 expression in synovial fibroblasts from patients with rheumatoid arthritis. Issue 01 (10th March 2009) - Warstat, K; Hoberg, M; Rudert, M; Tsui, S; Pap, T; Angres, B; Essl, M; Smith, T J; Cruikshank, W W; Klein, G; Gay, S; Aicher, W K
Abstract : Objectives: In synovial tissues of patients with rheumatoid arthritis (RA), strong expression of laminins and integrins co-localises with increased expression of inflammatory cytokines. Synovial fibroblasts (SF) contribute to the pathogenesis of RA through increased expression of cytokines and chemoattractant factors, one of which is interleukin-16 (IL16). A study was undertaken to investigate the regulatory pathways of IL16 in SF from patients with RA (RA-SF) and osteoarthritis (OA-SF). Methods: SF were seeded in laminin-coated flasks and activated by the addition of cytokines. The expression of IL16 was investigated by quantitative RT-PCR, immunoblotting and ELISA; its biological activity was determined by a cell migration assay. Cell–matrix interactions were investigated by cell binding and attachment assays. Relevant intracellular signalling pathways were studied by immunoblotting and with pharmacological blocking reagents. Results: Stimulation of SF with transforming growth factor β1 (TGF-β1 ) and growth on laminin-111 (LM-111) significantly increased the expression of IL16. Binding to LM-111 induced significantly more IL16 mRNA in RA-SF than in OA-SF (p<0.05). The IL16 cytokine was detected in supernatants of TGF-β1 -activated and in LM-111+TGF-β1 -activated RA-SF (38 to 62 pg/ml), but not in supernatants of OA-SF. This IL16 regulation involved p38MAPK, ERK1/2 and SMAD2 signalling, but not NFκB. Conclusions: Binding of RA-SF to LM-111 in the presence of TGF-β1 triggers a significant IL16 response and thus may contribute to the infiltration of CD4+ lymphocytes into synovial tissues. This mode of IL16 induction represents a novel pathway leading to IL16 production in RA-SF but not in OA-SF, which operates independently of NFκB signalling.